Indian media professionals’ perspectives regarding the role of media in suicide prevention and receptiveness to media guidelines: a qualitative study - Lakshmi Vijayakumar; Gregory Armstrong; Anish Cherian; Soumitra Pathare; Kannan Krishnaswamy (BMJ Open)
Objectives Crime reports of suicide incidents routinely feature in the Indian mass media, with minimal coverage of suicide as a broader public health issue. To supplement our recently published content analysis study, we undertook qualitative interviews to examine media professionals' perspectives and experiences in relation to media reporting of suicide-related news in India.Design and setting In 2017–2018, we undertook semistructured qualitative interviews with media professionals with experience reporting on suicide-related news. A semistructured interview guide was designed to initiate discussions around their perspectives and experiences in relation to reporting on suicide. Interviews were digitally audio-recorded and transcribed, and a deductive and inductive approach to thematic analysis was used.Participants Twenty-eight interviews were undertaken with media professionals in Delhi, Chandigarh and Chennai.Results A clear role for media in suicide prevention framed around educating and informing the public was articulated by several participants and a majority of participants also reported concerns and anecdotal accounts that their reporting may negatively influence vulnerable people in the population. Nonetheless, a fatalistic attitude towards suicide was evident among several participants including dismissing or minimising concerns around imitation suicides. Several participants also expressed doubts around the quality of suicide helplines in India and were hesitant to add such contact details to their reports. Participants were largely very receptive to the idea of developing voluntary media guidelines for the Indian context, although doubts were raised around compliance unless additional initiatives were taken to engage media professionals at the highest levels.Conclusions Our findings reveal the perspectives of media professionals operating in the Indian context and can be used to support constructive partnerships between media professionals and suicide prevention experts. There is a clear need for a genuine and sustained partnership between suicide prevention experts and media professionals at all levels.